If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5x-66)-30=(5x-66)
We move all terms to the left:
(5x-66)-30-((5x-66))=0
We get rid of parentheses
5x-((5x-66))-66-30=0
We calculate terms in parentheses: -((5x-66)), so:We add all the numbers together, and all the variables
(5x-66)
We get rid of parentheses
5x-66
Back to the equation:
-(5x-66)
5x-(5x-66)-96=0
We get rid of parentheses
5x-5x+66-96=0
We add all the numbers together, and all the variables
-30!=0
There is no solution for this equation
| -3(3)+y=15 | | X^2+x+7=19 | | 6x=2x^2/3 | | -8p+3=-125 | | 2x5=17 | | 36=((2x+2)(3x))/2 | | x-5(-4)=20 | | u/2+11=26 | | 72=6x(x+1) | | (x2+6x+9)3/4-13=14 | | -3(x+5)-2=-32 | | |2x|=4 | | 6x2+-14x+4=0 | | 4x-1=9x-22 | | 3(x-3)-12=-9 | | 68+y=96+X | | 3+9p^2=4 | | (6x+6x)+3(2+3)=39 | | 10x+4=1440 | | 5(x+1)+5=-10 | | 6x-2=5x+36 | | 10x-10x+2x=20 | | 12=x÷5-8 | | -87x=135 | | 8x-1=7x+19 | | 8x-1=6x-2 | | 8x-1=5x+36 | | 5(x+5)+4=49 | | 4(x-6)+5=-3 | | 8x-14=6x-8 | | 30=y/5+11 | | y÷5=10 |